2023
DOI: 10.1002/jmv.28553
|View full text |Cite
|
Sign up to set email alerts
|

“Mitochondrial pathogenic mutations and metabolic alterations associated with COVID‐19 disease severity”

Abstract: The severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) caused global pandemic and drastically affected the humankind. Mitochondrial mutations have been found to be associated with several respiratory diseases. Missense mutation and pathogenic mitochondrial variants might unveil the potential involvement of the mitochondrial genome in coronavirus disease 2019 (COVID‐19) pathogenesis. The present study aims to elucidate the role of mitochondrial DNA (mtDNA) mutations, mitochondrial haplogroup, and ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Specifically, Dirican and colleagues [43] by Sanger sequencing of two specific genes, ATPase6 and Cytb, found that COVID-19 patients displayed more A8860G and G9055A substitutions in the ATPase6 gene and more A15326G, T15454C, and C15452A changes in the Cytb gene. Kumari et al, analyzed whole mtDNA genome by NGS and discovered 15 highly conserved and pathogenic variants associated with COVID-19 in genes of mitochondrial complex I and complex IV [22]. Interestingly, we also found an increase of heteroplasmic variant burden in COVID-19 patients in genes of the same respiratory complexes.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Specifically, Dirican and colleagues [43] by Sanger sequencing of two specific genes, ATPase6 and Cytb, found that COVID-19 patients displayed more A8860G and G9055A substitutions in the ATPase6 gene and more A15326G, T15454C, and C15452A changes in the Cytb gene. Kumari et al, analyzed whole mtDNA genome by NGS and discovered 15 highly conserved and pathogenic variants associated with COVID-19 in genes of mitochondrial complex I and complex IV [22]. Interestingly, we also found an increase of heteroplasmic variant burden in COVID-19 patients in genes of the same respiratory complexes.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, the mtDNA analyzed in this study, deriving from middle-old and oldest-old individuals, might have been subjected to repeated events of oxidative stress, resulting in increase of transversions, although this issue has been strongly questioned in recent years, [41,42]. Two previous investigations studied mtDNA variants associated with COVID-19 and they both demonstrated an increment in patient group vs. controls [43,22]. Specifically, Dirican and colleagues [43] by Sanger sequencing of two specific genes, ATPase6 and Cytb, found that COVID-19 patients displayed more A8860G and G9055A substitutions in the ATPase6 gene and more A15326G, T15454C, and C15452A changes in the Cytb gene.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation